2004
DOI: 10.1152/ajplung.00268.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sham air and cigarette smoke on A549 lung cells: implications for iron-mediated oxidative damage

Abstract: Inhalation of airborne pollution particles that contain iron can result in a variety of detrimental changes to lung cells and tissues. The lung iron burden can be substantially increased by exposure to cigarette smoke, and cigarette smoke contains iron particulates, as well as several environmental toxins, that could influence intracellular iron status. We are interested in the effects of environmental contaminants on intracellular iron metabolism. We initiated our studies using lung A549 type II epithelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…Hence, to elucidate the molecular mechanisms for free iron accumulation linked to ferroptosis induction in COPD pathogenesis, we focused on NCOA4-mediated ferritinophagy in a CSE-treated bronchial epithelial cell. A recent study demonstrated that intracellular ferritin is transiently increased by CS, but declines after long time CS exposure, reflecting iron mobilization from ferritin in A549 cells 26 . In agreement with this observation, CSE treatment transiently increased ferritin expression, which was shifted to a time-dependent attenuation at 6 h with concomitant upregulation of NCOA4 in BEAS-2B (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Hence, to elucidate the molecular mechanisms for free iron accumulation linked to ferroptosis induction in COPD pathogenesis, we focused on NCOA4-mediated ferritinophagy in a CSE-treated bronchial epithelial cell. A recent study demonstrated that intracellular ferritin is transiently increased by CS, but declines after long time CS exposure, reflecting iron mobilization from ferritin in A549 cells 26 . In agreement with this observation, CSE treatment transiently increased ferritin expression, which was shifted to a time-dependent attenuation at 6 h with concomitant upregulation of NCOA4 in BEAS-2B (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…In vertebrate cells, IRP1 exists with a disulfide bridge; a form that does not bind to the IRE. The addition of reducing agent to cytoplasmic extracts of human cells (Mayo et al, 2004) or to the rHIRP1 (Gray et al, 1993) reduces this bridge and thereby, increases IRP1 binding activity. We evaluated the effects of b-mercaptoethanol (bME) on mosquito IRP1/ IRE interaction of cytoplasmic extracts from CCL-125 cells.…”
Section: Mosquito Irp1/ire Binding Activitymentioning
confidence: 99%
“…Raji B, Caco-2, and HT29-MTX cells were seeded separately and in triple cell culture and incubated for 24 h at 37 • C in 5% CO 2 environment. MTS solution was added to each cell culture per the manufacturer's directions [38,39]. After a 2-h 37 • C incubation, the absorbance was measured at 490 nm using a plate reader (Synergy, BioTek, Winooski, VT, USA).…”
Section: Methodsmentioning
confidence: 99%